Study between Fracture Fixation of Patella with Cerclage and Tension Band Wiring Technique - Aakash Sharma1 , Nitin Samal2 , Kunal Saoji3 , Vasant Gawande4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction: In human body among the skeletal system patella is the largest sesamoid bone in thequadriceps tendon in the body. Surgery is required for about one third of patella facture that indicateddamage to the extensor mechanism. Regarding treatment of patellar fracture there is a controversy sinceearliest time. TBW is consider as current gold standard for the displaced transverse patella fractures whereassome surgeons recommend augmentation of TBW with circumferential cerclage wiring to enhance thestrength of the fixation.Aim: The main aim was study between fracture fixation of patella with cerclage and Tension Band Wiringtechnique.Material and Method: Total 62 patients with fracture of patella were included in this study with the agemore than 20 years. Almost for all the patients surgery was performed and tourniquet was also used. Byusing a midline longitudinal incision surgery was done over anterior aspect of the knee. By using tensionband wiring with or without augmented cerclage with stainless steel wire open reduction and internal fixationwere done. After the surgery as post operative knee brace was given so that patients could start range ofmotion at knee without pain. To make sure that whether proper fixation was done or not Post-operativeradiographs were also done.Result: In study total 50 patients were included in which 34(68%) were male and 16(32%) were female.Among 50 patients was included different age group in which more patients were in the age group of 40-50years old as 36%.Conclusion: In the facture of patella modified TBW was better than encirclage wiring in treatment probablybecause of good stability of implant and easier postoperative rehabilitation. Hence use of circumferentialcerclage wiring along with tension band wiring for fractures of patella has no added advantage over fixationwith tension band wiring alone.